An information economics perspective on main bank relationships and firm R&D - Daniel Hoewer; Tobias Schmidt; Wolfgang Sofka (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2011)
Information economics has emerged as the primary theoretical lens for framing financing decisions in firm R&D investment. Successful outcomes of R&D projects are either ex-ante impossible to predict or the information is asymmetrically distributed between inventors and investors. As a result, bank lending for firm R&D has been rare. However, firms can signal the value of their R&D activities and as a result reduce the information deficits that block the availability of external funding. In this study we focus on three types of signals: Firm's existing patent stock, the presences of a joint venture investor and whether the firm has received a government R&D subsidy. We argue theoretically that all of these signals have the potential to alter the risk assessment of the firm's main bank. Additionally, we explore heterogeneities in these risk assessments arising from the industry level and the main bank's portfolio. We test our theoretical predictions for a sample of more than 7,000 firm observations in Germany over a multi-year period. Our theoretical predictions are only supported for firms' past patent activity while other signals fail to alter the risk assessment of a firm's main bank. Besides, we confirm that the risk evaluation is not randomly distributed across bank-firm dyads but depends on industry and bank characteristics.
Keywords: O32; D82; G30; 330; Innovation; banking; information asymmetry; Forschungsfinanzierung; Industrielle Forschung; Signalling; Bank; Lieferanten-Kunden-Beziehung; Kreditgeschäft; Asymmetrische Information; Theorie; Schätzung; Deutschland